Can nurses be key players in assessing early motor development using a structured method in the child health setting?. Issue 4 (11th May 2015) - Johansen, Kine; Persson, Kristina; Sarkadi, Anna; Sonnander, Karin; Magnusson, Margaretha; Lucas, Steven
Abstract Rational, aims and objectives Increasing evidence highlights the importance of early interventions for motor disorders in children. Given the key medical role of the nurse within the Swedish Child Health Service (CHS), we aimed to examine if nurses could apply a structured assessment of early motor development at the child health centre to enable early identification of children at risk. Methods Structured Observation of Motor Performance in Infants (SOMP‐I) assesses infant's level of motor development and quality of motor performance using subscales converted to total scores. The total score for both level and quality can then be plotted within the SOMP‐I percentile distribution at the child's age for comparison with a reference population. Fifty‐five infants (girls: 30) were assessed according to SOMP‐I at three child health centres. Assessments were performed by nurses (n = 10) in a clinical setting; one nurse performed the assessment while another nurse and a physiotherapist observed. Results Agreement for the assessment of level as a continuous variable was excellent [intraclass correlation coefficient (ICC) 0.97–0.98], but was lower for quality (ICC 0.02–0.46). When the children were categorized according to the percentile range categories, the assessors were in agreement for the majority of the children, with respect to both level (78–82%) and quality (78–87%). Conclusion Despite brief experience with SOMP‐I, the agreement was excellent when assessing the level of motor development, but was less satisfactory for the assessment of quality of motor performance. More extensive education and training may be necessary to improve the nurses' ability to assess quality, as this domain was an entirely new concept to the nurses. Further research is warranted to determine the applicability of SOMP‐I as a standardized method for nurses to assess motor development within the CHS.